The Influence of Digital Sharia Banking Services on the Digital Financial Literacy of Generation Z in Malang City - Shalshabilla Putri; Rini Safitri (al-Afkar, Journal For Islamic Studies, 2025)
The aim of this research is to determine the influence of digital sharia banking services on the digital financial literacy of generation z in Malang City. This study including in type study quantitative. Object for this study is generation z in Malang City consisting of from 100 respondents . Retrieval technique sample use technique purposive sampling. Data collection techniques through spread questionnaires and for technique data analysis using simple regression analysis​​ linier with SPSS software. The variables studied​ are Digital Services (X) and Digital Financial Literacy (Y). The research results show that digital services provided by sharia banking have a significant and positive effect on the digital financial literacy of generation z in Malang City. It means that every additional digital sharia banking service can increase the digital financial literacy of generation z in Malang City.